Kendala Orang Tua Belajar Dari Rumah (BDR) Dengan Sistem Pembelajaran Daring Pada Masa Pandemi Di TK Negeri Pembina Kabupaten Tanah Datar - Marliza, Suci; Hartati, Sri (Universitas Pendidikan Indonesia Kampus Serang, 2021)
The implementation of online learning in reality has many obstacles for parents when accompanying children to study at home. The purpose of this study is (1) to find out the obstacles faced by parents when their children learn from home, (2) to find out the efforts taken by parents to deal with the obstacles they face while their children are learning from home. This study uses a quantitative descriptive approach with data collection techniques using a questionnaire. The methodology used in this research is descriptive quantitative by distributing questionnaires to respondents, namely the children's parents. The results of the study stated that (1) understanding of the subject matter by parents as many as 38 parents (76%) understanding of the subject matter by parents had not been able to understand the subject matter that had been given by the teacher. (2) When parents accompany their children to study at home, 39 parents (78%) cannot accompany their children to study at home. (3) Parents' obstacles in using this gadget can be seen from 29 parents (58%) who are unable to operate the gadget properly. By knowing these challenges, it is hoped that in the future parents can anticipate the learning process well during the pandemic.